Review of Maqāshid al Syarī’ah Regarding Grants Counted as Inheritance in Article 211 of the Compilation of Islamic Law - Sulaiman, Mursalin (Al-Fikrah, 2024)
A gift (hibah) involves the transfer of property to another without compensation during the giver's life, often to prevent disputes after their death. In Islamic law, hibah to non-heirs, like adopted children, can create issues. Article 211 of KHI limits hibah to a maximum of one-third of the benefactor's wealth, safeguarding legitimate heirs' rights. Maqāshid al-syarī’ah views hibah as a means to ensure the welfare of all, including the protection of wealth and lineage. This study examines hibah in Article 211 of KHI and analyzes it through maqāshid al-syarī’ah. Using a qualitative library approach, findings show that hibah given during the benefactor's lifetime may be counted in the inheritance to maintain fairness among heirs. Maqāshid al-syarī’ah stresses justice, family harmony, and collective welfare, aiming to prevent conflict and uphold balanced rights among heirs and the benefactor’s intentions.